An algorithm for rapid computational construction of metabolic networks: A cholesterol biosynthesis example - Diane Kelly (Computers in Biology and Medicine, 2013)
Alternative pathways of metabolic networks represent the escape routes that can reduce drug efficacyand can cause severe adverse effects. In this paper we introduce a mathematical algorithm and a codingsystem for rapid computational construction of metabolic networks.The initial data for the algorithmare the source substrate code and the enzyme/metabolite interaction tables.The major strength of thealgorithm is the adaptive coding system of the enzyme–substrate interactions. A reverse application ofthe algorithm is also possible,when optimisation algorithm is used to compute the enzyme/metaboliterules from the reference network structure.The coding system is user-defined and must be adapted tothe studied problem.The algorithm is most effective for computation of networks that consist ofmetabolites with similar molecular structures.The computation of the cholesterol biosynthesismetabolic network suggests that 89 intermediates can theoretically be formed between lanosteroland cholesterol,only 20 are presently considered as cholesterol intermediates.Alternative metabolitesmay represent links with other metabolic networks both as precursors and metabolites ofcholesterol. Apossible cholesterol-by-pass pathway to bile acids metabolism through cholestanol is suggested.